Cartography - Perry, Everett (New York Magnum Publishing, 2016)
"The study and practice of making maps is referred to cartography. Combining science, aesthetics, and technique, cartography builds on the basis that authenticity can be modeled in ways that link spatial information efficiently. Modern cartography, mostly integrated with geographic information science, organizes many theoretical and practical fundamentals of geographic information systems. In cartography, technology has continually changed in order to meet the demands of new generations of mapmakers and map users. The creation of more accurate maps and the ability to store and manipulate them digitally has evolved with the advent of magnetic devices. This book details the fundamentals and recent advances in cartography."--Amazon.
Ms. Cora Jane Lawas (Recommending faculty) - Bookfair 2019
Keywords: Cartography